Hot response - Stacey, Shannon (Stacey, Shannon. Boston Fire., 2018)
Gavin Boudreau lives for the job, but he also believes in "work hard, play harder." As the youngest guy in Ladder 37, he figures he's got plenty of time before settling down becomes a priority. Soft, pretty women who aren't looking for promises are exactly his type, and he's comfortable with that. Working with a gorgeous EMT isn't going to change who he is. The last thing Cait Tasker needs in her personal life is a firefighter whose challenges on-scene have been a thorn in her side from minute one. Her plate's too full for a man anyway. Back in her childhood home to help her family cope with an unexpected tragedy, she's got enough to handle without throwing a hot, testosterone-laden fireman into the mix. As long days on the job lead to long nights together, Gavin and Cait will discover how far temptation can take them - and what happens when the one you thought was all wrong for you turns out to be the person you can't live without.